Mesangial Cell-Specific Antibodies Are Central to the Pathogenesis of Lupus Nephritis - Guillaume Seret; Yannick Le Meur; Yves Renaudineau; Pierre Youinou (Clinical and Developmental Immunology, 2012)
Not only is nephritis a common complaint in systemic lupus erythematosus, but it is also the most life-threatening complication of the disease. Anti-double-stranded DNA antibodies (Abs), which are found in up to 80% of these patients, might be nephritogenic per se. That is, they may cross-react with mesangial cell (MC) surface proteins, such as alpha-actinin and annexin A2, they may cross-react with mesangial matrix protein such as laminine and fibronectin, or they may recognize chromatin material previously deposited in the glomeruli. The consequence of the binding of anti-MC Abs may be their internalization, which results in activation and proliferation of these MCs. In turn, these activated MCs are suspected of promoting immune complex formation by sequestering and thereby protecting chromatin from degradation. The present paper will explain the mechanisms through which such autoAbs may initiate nephritis.